The influence of chain extender on properties of polyurethane-based phase change materials modified with graphene. (15th January 2016) - Pielichowska, Kinga; Nowak, Michał; Szatkowski, Piotr; Macherzyńska, Beata
Graphical abstract: Highlights: Polyurethane/graphene composites with solid–solid phase transition were obtained. PEG incorporated as a soft segment acts as PCM with high heat of phase transition. The influence of chain extender on PU PCMs properties was investigated. Graphene introduction caused an increase in thermal stability and conductivity. Abstract: In this paper polyurethane-based phase change materials (PCMs) modified with graphene for thermal energy storage were obtained in situ using a one-step bulk polymerization method. Polyurethanes (PUs) have been synthesized with 1, 4-butanediol as a chain extender or without a chain extender. FTIR-ATR, DSC, TGA, SEM, OM and ultrasonic techniques were used for characterization of the obtained composites containing up to 4 wt.% of graphene. FTIR-ATR analysis confirmed PU structure and proved that there was no chemical reaction between polyurethane and graphene. The highest heat of phase transition and crystallinity were found for PU system synthesized without the chain extender and modified with 1.0 wt.% of graphene. Microscopic observation results indicated spherulite structures typical for poly(ethylene glycol) (PEG) which was used to form soft segments, with regions of lamellar crystal bundles radiating from the center of a spherulite. Thermal cycling tests were done by 50 and 100 heating/cooling cyclings in air and nitrogen atmosphere for verification of the thermal reliability and chemical stability – it has been found the heat of phase transition was generally not diminished. Importantly, the thermal conductivity of the PCMs was improved after modification with graphene. Generally, PUPEG without chain extender exhibited higher heat of phase transition, higher thermal stability and better thermal reliability.